2022
DOI: 10.3390/diagnostics12020326
|View full text |Cite
|
Sign up to set email alerts
|

Mesonephric-like Adenocarcinoma of the Ovary: Clinicopathological and Molecular Characteristics

Abstract: Mesonephric-like adenocarcinoma (MLA) arising in the ovary is a rare malignant tumor of the female genital tract. Although the clinicopathological and molecular characteristics of uterine MLA have been accumulated, those of ovarian MLA have not been firmly clarified. In this study, we investigated the clinicopathological, immunohistochemical, and genetic features of five ovarian MLAs. A review of electronic medical records and pathology slides, immunostaining, and targeted sequencing was performed. On imaging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(68 citation statements)
references
References 53 publications
2
53
2
Order By: Relevance
“…For CD10, we examined the subcellular localization of positive immunoreactivity. In particular, CD10 immunoreactivity along the luminal surfaces of neoplastic tubules and ducts was considered as positive expression, supporting the diagnosis of MLA (2,5). p53 expression was interpreted as having a mutated pattern when one of the following staining patterns was observed: diffuse and strong nuclear immunoreactivity in ≥75% of the tumor cells (over-expression pattern); no nuclear immunoreactivity in any of the tumor cells (complete absence pattern); or an unequivocal cytoplasmic staining accompanied by variable nuclear staining (cytoplasmic pattern) (28).…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…For CD10, we examined the subcellular localization of positive immunoreactivity. In particular, CD10 immunoreactivity along the luminal surfaces of neoplastic tubules and ducts was considered as positive expression, supporting the diagnosis of MLA (2,5). p53 expression was interpreted as having a mutated pattern when one of the following staining patterns was observed: diffuse and strong nuclear immunoreactivity in ≥75% of the tumor cells (over-expression pattern); no nuclear immunoreactivity in any of the tumor cells (complete absence pattern); or an unequivocal cytoplasmic staining accompanied by variable nuclear staining (cytoplasmic pattern) (28).…”
Section: Methodsmentioning
confidence: 69%
“…A unique immunophenotype of MLA has also been documented in the literature (2,6,13,14). The following expression patterns support the diagnosis of MLA: positive immunoreactivities for mesonephric markers, including GATA-binding protein 3 (GATA3), paired box 2 (PAX2), transcription termination factor 1 (TTF1), and cluster of differentiation 10 (CD10); negative or only focal expression of hormone receptors; non-diffuse p16 positivity; and wild-type p53 immunostaining pattern (1,2,5,6,8,9). Molecular studies using targeted next-generation sequencing (NGS) revealed that patients with uterine MLA frequently harbor a pathogenic mutation in the Kirsten rat sarcoma viral oncogene homolog (KRAS) gene, as well as alterations in neuroblastoma viral oncogene homolog, AT-rich interaction domain (ARID1A), phosphatidylinositol-4,5bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), βcatenin, patched 2, and tumor protein 53 (TP53) (1,8,9,15).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…9 However, the subset of mesonephric-like tumors with frankly malignant sarcomatous elements or heterologous differentiation may be classified as mesonephric-like carcinosarcoma. 25,26,42 As the sarcomatous elements of mesonephric-like carcinosarcoma are negative for GATA3 and TTF1 14,26 and heterologous elements may be seen in both mesonephric-like and conventional uterine carcinosarcoma, careful examination of the associated carcinomatous elements is necessary for classification. The natural history of mesonephric-like carcinosarcoma (and thus the significance of distinguishing this rare entity from conventional uterine carcinosarcoma) is uncertain.…”
Section: Other Endometrial Carcinomasmentioning
confidence: 99%
“…However, accumulated evidence disclose MLAs do not infrequently harbor PIK3CA and PTEN alterations which are commonly seen in endometrial endometrioid carcinomas (EECs) but are very rare in MAs (11,13,16). Furthermore, extra-uterine MLAs are often associated with Müllerian lesions such as endometriosis and serous tumors (17)(18)(19)(20). This evidence has led some pathologists to suggest that MLA may represent mesonephric-like transdifferentiation of a Müllerian tumor rather than a true mesonephric tumor (9,11,13,16).…”
Section: Introductionmentioning
confidence: 99%